Human Papillomavirus-related Oropharyngeal Cancer: Are Recurrences Similar to the Parent Tumor? - Vainshtein, Jeffrey (2014)
BACKGROUND: Although typically associated with a favorable prognosis, a minority of human papillomavirus (HPV)-related oropharyngeal cancers (OPC) recur after chemoradiation. We postulated that a minor HPV-negative tumor sub-fraction may be responsible for recurrences of HPV+ OPC. METHODS: Paired untreated primary and recurrent tumor specimens were identified for 37 OPC patients who received definitive chemoradiotherapy at our institution. Concordance in HPV/p16 expression between primary and recurrent tumors was assessed. RESULTS: Among 31 patients with HPV+/p16+ primary tumors, 30 (97%) retained evidence of both HPV and p16+ expression at recurrence (27 HPV+/p16+; 3 HPV+/p16-partial). One (3%) initially HPV+/p16+ patient developed a HPV-/p16- lung squamous cell carcinoma, representing either a discordant OPC metastasis or second primary tumor. CONCLUSION: HPV-related OPCs retain HPV+/p16+ expression at recurrence. Our results fail to provide evidence that a minor HPV-negative tumor sub-fraction is responsible for biologically aggressive behavior of HPV+ OPC that recurs after chemoradiation.